Imaging in myeloma: a Royal College of Radiologists national survey of current imaging practice. Issue 11 (November 2021) - Westerland, O.; Drinkwater, K.J.; Parikh, J.; Streetly, M.; Pratt, G.; Goh, V.; Howlett, D.C.
Abstract : Aims: To evaluate current national imaging practice in myeloma with reference to National Institute for Health and Care Excellence (NICE) guidelines (NG35, 2016) and compare results with an initial survey conducted in 2017 (61 participating sites). Materials and methods: All UK radiology departments treating myeloma patients and with a Royal College of Radiologists (RCR) Audit Lead were invited to participate. Data were collected using an online questionnaire. Descriptive statistics were performed. Results: One hundred and fourteen hospitals supplied data (54% return rate). Skeletal survey (SS) remains the most-commonly performed first-line imaging test for suspected/confirmed myeloma or plasmacytoma (39%, 45/114 hospitals), followed by whole-body magnetic resonance imaging (WBMRI) (27%, 31/114) and whole-body computed tomography (WBCT) (19%, 22/114). Integrated positron-emission tomography/CT (PET/CT) was first-line in 14% (16/114). The NICE recommended initial investigation, WBMRI, is currently offered in 27% of surveyed hospitals (<10% in 2017). Ongoing challenges to implementing WBMRI include scanner availability, financial constraints, reporting time, and radiologist training. Conclusion: Despite NICE recommendations regarding WBMRI in diagnosis/follow-up of myeloma, SS (poor sensitivity and specificity) remains the most commonly performed first-line test. Radiologists, haematologists, and patients should continue to emphasise the superiority and benefit of modern and more accurate imaging, such that they are prioritised in clinical service planning. Highlights: WBMRI is recommended by NICE and BSH in management of myeloma and plasmacytoma. Despite recommendations, WBMRI is only offered in 27% of surveyed hospitals. Challenges: scanner availability, cost, reporting time, radiologist training.